Chromatin structure with respect to histone signature changes during cell differentiation - Harnicarová Horáková, Andrea; Bártová, Eva; Kozubek, Stanislav (Cell structure and function, 2010)
Here, we would like to point out important milestones in the study of nuclear radial positioning and gene expression during differentiation processes. In addition, changes in the histone signature that significantly precede various differentiation pathways are reviewed. We address the regulatory functions of chromatin structure and histone epigenetic marks that give rise to gene expression patterns that are specific to distinct differentiation pathways. The functional relevance of nuclear architecture and epigenetic traits is preferentially discussed in the context of in vitro induced enterocytic differentiation and pluripotent or differentiated embryonic stem cells. We especially focus on the recapitulation of nuclear events that have been characterized for some genes and proto-oncogenes that are important for development and differentiation.
Keywords: buněčná diferenciace; embryonální kmenové buňky; Chromatin; Humans; Gene Expression Regulation; Embryonic Stem Cells; chromatin; lidé; Histones; Pluripotent Stem Cells; pluripotentní kmenové buňky; histony; regulace genové exprese; Cell Differentiation